New Insights into Structural Evolution of LiNiO2 Revealed by Operando Neutron Diffraction. Issue 11 (18th October 2021) - Chien, Po‐Hsiu; Wu, Xianyang; Song, Bohang; Yang, Zhijie; Waters, Crystal K.; Everett, Michelle S.; Lin, Feng; Du, Zhijia; Liu, Jue
Abstract: Invited for this month's cover picture is the group of Jue Liu and co‐workers. The front cover shows the operando neutron diffraction study of structural evolution of LiNiO2 cathode in a jelly‐type full cell. The anomalous increase of Ni−O bond length at high degrees of charge is successfully captured, bringing new insights into the structure and electronic structure evolution of LiNiO2 at deep charging states. Read the full text of the Article at 10.1002/batt.202100135 . Abstract : "It has been long believed that average Ni−O bond length decreases during charge, but our discovery of the anomalous increase of Ni−O bond lengths at high degrees of charge suggests that the charge compensation mechanism is more complicated in the deeply charged Lix NiO2 …" Learn more about the story behind the research featured on the front cover in this issue's Cover Profile. Read the corresponding Article on 10.1002/batt.202100135 .